2019
DOI: 10.1186/s12879-019-4011-6
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of mumps and meteorological factors in Beijing, China

Abstract: Background Over the past decades there have been outbreaks of mumps in many countries, even in populations that were vaccinated. Some studies suggest that the incidence of mumps is related to meteorological changes, but the results of these studies vary in different regions. To date there is no reported study on correlations between mumps incidence and meteorological parameters in Beijing, China. Methods A time series analysis incorporating selected weather factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
1
13
0
3
Order By: Relevance
“…However, our result differed from that of a study conducted in Ireland, which detected a relatively low mumps incidence in summer and a peak in autumn [7], and a study conducted in the Netherlands with two seasonality peaks in spring and autumn [26]. In China, the epidemic pattern in Guanghzou also differed from that of Beijing city, Zibo city in Shandong province, and Chongqing city, which showed two epidemic peaks from April to July and October to January, with an emphasis on the former [17,27,28]. It indicated that the effect of meteorological factors on the occurrence of mumps may be distinct in various regions with particular climatic features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our result differed from that of a study conducted in Ireland, which detected a relatively low mumps incidence in summer and a peak in autumn [7], and a study conducted in the Netherlands with two seasonality peaks in spring and autumn [26]. In China, the epidemic pattern in Guanghzou also differed from that of Beijing city, Zibo city in Shandong province, and Chongqing city, which showed two epidemic peaks from April to July and October to January, with an emphasis on the former [17,27,28]. It indicated that the effect of meteorological factors on the occurrence of mumps may be distinct in various regions with particular climatic features.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies showed different results. For instance, a study conducted in 10 cities in Guangxi province in China [20] reported that no significant relationship was found between atmospheric pressure and the incidence of mumps, whereas a study conducted in Beijing [17] showed that atmospheric pressure was negatively associated with mumps incidence. Unfortunately, limited studies are available regarding the underlying mechanism.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The well-known ARIMA model is widely used in time series analysis for describing and predicting epidemic prevalence for its accuracy and practicality [12][13][14]. The seasonal ARIMA (SARIMA) model that is developed from the ARIMA model, incorporates seasonal period and performs better in the presence of an obvious seasonal pattern.…”
Section: Construction Of Sarima Modelmentioning
confidence: 99%
“…Diferentemente dos artigos supracitados, neste trabalho, uma série temporal de dados de focos de calor no Brasilé analisada, através de técnicas de visualização de dados. Além disso, uma predição da tendência da quantidade de focos para três Estados brasileirosé avaliada, por meio do método de regressão SARIMAX [Hao et al 2019].…”
Section: Introductionunclassified